OPTIMASI PH ALUMINA DAN 99Mo DALAM PEMBUATAN GENERATOR 99Mo/99mTc BERBASIS MoO3 ALAM - Sulaiman; Sugiharto, Yono; Chairuman; Setiawan, Gatot; Gunawan, Adang Hardi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Alumina material has long been used for 99Mo radioisotope adsorbent in the 99Mo/99mTc generator. The 99Mo/99mTc generator produces 99mTc radioisotope which is used for the diagnostic purposein nuclear medicine. To date, alumina is used to adsorp 99Mo obtained from fission reaction of 235U. The restriction of the use of fission 235U leads to the find of an alternative 99Mo. The alternative of 99Mo production is obtained from natural MoO3 which is irradiated by thermal neutron in the nuclear reactor. The 99Mo radioisotope produced from this reaction has no carrier-free properties. This is due to the abundanceof natural MoO3 is 24.13%.In the99Mo/99mTc generator based on natural MoO3 by using alumina column, it is necessary to know the alumina type for optimum 99Mo adsorption, as well as pH of 99Mo. In this study, there were used three variations of alumina-based generator column namely acid, neutral, and basic alumina. The 99Mo solution used in this study was also performed three pH: pH 4, pH 7, and pH 8 of the 99Mo solution. The generator eluted and observed daily for 3 days and continued after the next two days for 2 days. The optimum adsorption of 99Mo from natural MoO3 by alumina material was given in the use of acidic alumina with the pH 4 of the99Mo solution. Among the three pH variation of the 99Mo solution, the 99Mo solution of pH 4 gives the highest of 99mTc yield. The column with the smallest 99Mo breakthrough is given by acidic alumina column using the 99Mo solution of pH 4. Thus, acidic alumina column can be used as an adsorbent to adsorp natural 99Mo.